Return to play after conservative treatment in athletes with symptomatic lumbar disc herniation: a practice-based observational study - Jun Iwamoto; Yoshihiro Sato; Tsuyoshi Takeda; et al (Dove Medical Press, 2011)
Jun Iwamoto1, Yoshihiro Sato2, Tsuyoshi Takeda1, Hideo Matsumoto11Institute for Integrated Sports Medicine, Keio University School of Medicine, Tokyo, Japan; 2Department of Neurology, Mitate Hospital, Fukuoka, JapanAbstract: The purpose of the study was to confirm the short-term outcome of conservative treatment in terms of the ability to return to play and factors influencing return to play in athletes with symptomatic lumbar disc herniation. A total of 100 consecutive athletes (72 male and 28 female) who consulted our sports medicine clinic during the 16-year period between September 1993 and October 2009 because of severe low back pain and/or leg pain/numbness due to lumbar disc herniation were studied. The mean age of the subjects was 23 years. All of them were conservatively treated by being advised to discontinue their sporting activities with/without short-term medication. After the subjective symptoms had reduced by more than 80%, individual training was started in order to allow the athletes to return to play. Seventy-nine athletes (79.0%) returned to play at an average of 4.8 months (range 1–12 months) after the start of treatment and were able to sustain the activities for at least 6 months, the minimum duration of follow-up in the study. The outcome of the conservative treatment was not influenced by the intensity of the sporting activity. Multiple logistic regression analyses showed that the severity of the symptoms prior to the start of treatment was the factor influencing the ability of the athletes to return to play. The present study confirmed the satisfactory short-term outcome of conservative treatment in athletes with symptomatic lumbar disc herniation regarding return to play and revealed that subjective symptoms prior to the start of treatment appeared to be a key factor in return to play after conservative treatment.Keywords: lumbar disc herniation, athletes, return to play, conservative treatment, sciatica, low back pain